Targeting TRPV1 as an Alternative Approach to Narcotic Analgesics to Treat Chronic Pain Conditions - Premkumar, Louis S. (Springer US, 2010)
In spite of intense research efforts and after the dedicated Decade of Pain Control and Research, there are not many alternatives to opioid-based narcotic analgesics in the therapeutic armamentarium to treat chronic pain conditions. Chronic opioid treatment is associated with sedation, tolerance, dependence, hyperalgesia, respiratory depression, and constipation. Since the affective component is an integral part of pain perception, perhaps it is inevitable that potent analgesics possess the property of impacting pain pathways in the supraspinal structures. The question still remains to be answered is that whether a powerful analgesic can be devoid of narcotic effect and addictive potentials. Local anesthetics are powerful analgesics for acute pain by blocking voltage-gated sodium channels that are involved in generation and propagation of action potentials. Antidepressants and anticonvulsants have proven to be useful in the treatment of certain modalities of pain. In neuropathic pain conditions, the complexity arises because of the notion that neuronal circuitry is altered, as occurs in phantom pain, in that pain is perceived even in the absence of peripheral nociceptive inputs. If the locus of these changes is in the central nervous system, commonly used analgesics may not be very useful. This review focuses on the recent advances in nociceptive transmission and nociceptive transient receptor potential vanilloid 1 channel as a target for treating chronic pain conditions with its agonists/antagonists.